STRATEGIC AND PRACTICAL DIRECTIONS OF ENVIRONMENTAL RISK ASSESSMENT (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The issues of environmental risk assessment in the frames of modern development of natural and human caused processes for the mountainous territories of the Republic of Armenia are considered. Specific models adequately reflecting this or that ecological situation are considered. This factor determines the prerequisites for the introduction of indicators of environmental risk, allowing to improve methods aimed at reducing social, economic and environmental consequences, natural disasters and their synergistic impact on the technosphere.
Keywords: ecological safety; modeling of ecosystems; mining; overpopulation; environmental pollution; National system of monitoring